Misidentification of Bellator gymnostethus (Gilbert, 1892) as Prionotus ruscarius Gilbert & Starks, 1904 (Scorpaeniformes: Triglidae) - Robertson, D. Ross; Angulo, Arturo; Baldwin, Carole C.; Pitassy, Diane; Driskell, Amy; Weigt, Lee; Navarro, Ignacio J.f. (Zootaxa, 2020)
The checklist by Robertson et al. (2017) of fishes from the tropical eastern Pacific included information on three members of the family Triglidae: Bellator loxias (Jordan, 1897), Prionotus ruscarius and P. stephanophrys Lockington, 1881. Unfortunately, the identification of four specimens as P. ruscarius is incorrect, as they are Bellator gymnostethus. We thank Benjamin Victor for bringing these misidentifications to our notice through his work with mtDNA sequence data from the Barcode of Life Database (BOLD: http://www.boldsystems.org). The photographs of the four specimens on the BOLD website clearly depict a Bellator species rather than a Prionotus. However, the photograph in the 2017 paper (Figure 75, page 78), is correctly identified and labelled as P. ruscarius, and this species was collected on the cruise of the Miguel Oliver discussed in Robertson et al. (2017), see Benavides Moreno et al. (2019). This correction brings the number of triglids collected on that cruise to four species.